The effect of flexing and personal branding on social media on the lifestyle of milenial Islamic students in Yogyakarta Indonesia - Puji Solikhah (Department of Islamic Economic, Faculty of Economic and Business, Nahdlatul Ulama Islamic University (UNISNU) Jepara, Indonesia, 2023)
This research motivated by the widespread behavior of flexing to promote personal branding by figures or public figures on social media. This research was conducted on millennial students in Yogyakarta, a research sample of 100 people was taken from millennial students who live and have the habit of living in Islamic boarding schools. The research method used is a descriptive quantitative method. The conclutions of this research that flexing variable (X1) has an effect on the lifestyle of millennial Islamic students by ( 1,824 ) or 18.24% and the personal branding variable (X2) has an effect on the lifestyle of millennial Islamic students partially by (3,239) or 32.39%. Based on the determination test, the variables X and Y have a joint effect of (4.023) or 40.23% and the rest are influences from outside these variables, which are equal to 50.77%..